Efeito do laser de baixa intensidade no col??geno tipo I e III na metaloproteinase de matriz em modelo experimental de tendinopatia induzida por colagenase em tend??o calc??neo de ratas idosas - Marques, Anna Cristina de Farias (2015)
This study investigates the effect of low-level laser therapy (LLLT) on collagen type I and III, matrix metalloproteinase (MMP), and vascular endothelial growth factor (VEGF) in experimentally induced tendinopathy in female aged rats. Tendinopathy was induced by collagenase peritendinous of the Achilles tendon. Forty-two Wistar rats (Norvegicus albinus) were used; groups consisted of 36 aged animals (18 months old; mean body weight, 517.7 ?? 27.54 g) and 6 adult animals (12 weeks old; mean body weight, 266 ?? 19.30 g). The animals were randomlydivided in three groups: control, aged tendinopathy, and aged tendinopathy LLLT; the aged groups were subdivided according to experimental periods: 7, 14, and 21 days. LLLT involved a gallium-arsenide-aluminum laser (Theralaser, DMC??) with active medium operating at wavelength 830 ?? 10 nm, 50 mW power, 0.028 cm2 laser beam, 107 J/cm2 energy density, 1.7 w/cm2 power density, and 6 J of energy, with a frequency of 3 times per week, until euthanasia. VEGF, MMP-3, and MMP-9 were analyzed by immunohistochemistry, and collagen type I and III by Sirius red. LLLT increased the deposition of collagen type I and III in a gradual manner, with significant differences relative to the group aged tendonitis (p<0.001), and in relation to VEGF (p<0.001); decreased expression of MMP-3 and 9 was observed in group aged tendinopathy (p<0.001). LLLT, therefore, increased the production of collagen type I and III, downregulated the expression of MMP-3 and MMP-9, and upregulated that of VEGF, with age and age-induced hormonal deficiency.